The Rome III Regulation : a commentary on the law applicable to divorce and legal separation - Corneloup, Sabine; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2020)
"This comprehensive Commentary provides an in-depth, article-by-article analysis of the Rome III Regulation, the uniform rules adopted by the EU to determine the law applicable to cross-border divorce and legal separation. Disputes on family matters form part of everyday litigation in the EU, with around 140,000 international divorces per year; this Commentary offers a clear legal understanding of the regulation that governs this increasingly significant area of family law. Written by a team of renowned experts on private international law in relation to family matters, chapters contextualise and examine the provisions of the regulation, with clear insight into the rationale behind the text. The contributors engage critically with each article, analysing Rome III's overall effectiveness and offering a balanced critique from a variety of European perspectives. Private international law scholars and practitioners alike will find this Commentary an incisive and useful point of reference. It will be of particular interest to those working in family law, including judges, lawyers, public notaries and family mediators, as well as graduate students looking for in-depth knowledge of the subject"--
Introduction / Sabine Corneloup -- Chapter I: Scope, relation with Regulation (EC) no 2201/2003, definitions and universal application -- Article 1. Scope / Susanne Lilian Gössl and Jinske Verhellen -- Article 2. Relation with Regulation (EC) No 2201/2003 / Sabine Corneloup -- Article 3. Definitions / Petra Hammje -- Article 4. Universal application / Fabienne Jault-Seseke -- Chapter II: Uniform rules on the law applicable to divorce and legal separation -- Article 5. Choice of applicable law by the parties / Cristina González Beilfuss -- Article 6. Consent and material validity / Natalie Joubert -- Article 7. Formal validity / Alexandre Boiché -- Article 8. Applicable law in the absence of a choice by the parties / Pietro Franzina -- Article 9. Conversion of legal separation into divorce / Laura Carpaneto -- Article 10. Application of the law of the forum / Bettina Heiderhoff -- Article 11. Exclusion of renvoi / Stefano Dominelli -- Article 12. Public policy / Bettina Heiderhoff -- Article 13. Differences in national law / Christelle Chalas -- Article 14. States with two or more legal systems - territorial conflicts of laws / Caroline Sophie Rupp -- Article 15. States with two or more legal systems - inter-personal conflicts of laws / Caroline Sophie Rupp -- Article 16. Non-application of this regulation to internal conflicts of laws / Caroline Sophie Rupp -- Chapter III: Other provisions -- Article 17. Information to be provided by participating member states / Alexandre Boiché -- Article 18. Transitional provisions / Cristina González Beilfuss -- Article 19. Relationship with existing international conventions / Thalia Kruger -- Article 20. Review clause / Sabine Corneloup -- Chapter IV: Final provisions -- Article 21. Entry into force and date of application / Sabine Corneloup -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: European Parliament; Evropská unie; evropské právo; rozvod; soudní rozhodnutí a stanoviska; European law; divorce; judgments; země Evropské unie; European Union countries; e-knihy online; e-books online